Strategi dan Implementasi Program CSR dalam Memberdayakan Ekonomi Lokal pada Program Bantuan Modal Kerja Bergulir UMKM - Nia Sarinastiti; Clara Subardjo (Jurnal InterAct, 2013)
This research discussed the strategy and implementation of a CSR program focusing  on  the  roll-over  credit  or  capital  loan  for  Micro,  Small  and Medium Enterprises byPT. Indocement Tunggal Prakarsa Tbk Citeureup (Indocement). The program distributes to villages around the company‘s operational activities.  The research applied a framework based on the CSR concept  relevant  to  corporate  social  marketing  for  community development, economic impact andtriple bottom line.   The qualitative method research conducted observation and in-depth interviews to relevant company representatives and beneficiaries. The result indicated that CSR strategy and implementation at Indocement has been able to mirror the triple bottom line concept, which means that some of its profit is used for community development in its surrounding area. The program has also provided direct and indirect economic impact to the communities.